Crude oil production and simulation from catalytic fast pyrolysis of waste polyethylene terephthalate (PET) - Avalos Ortecho, Edilberto Miguel (2025)
Polyethylene terephthalate (PET), a thermoplastic polymer, is the main raw material in the manufacturing of clear bottles used mainly for water and soft drinks. In 2022, the world plastics production was 400.3 million tons; around 6.2 % corresponds to PET, and only 10 % of it is recycled. PET waste can only be recycled four times because high temperatures generate chemical and physical degradation. This study aims to apply the principles of circular economy to transform PET waste into crude oil through fast catalytic pyrolysis, under N2 atmosphere at different temperatures and with different quantities of zeolite as a catalyst. The crude oil was characterized by Fourier-transform infrared spectroscopy (FTIR) and solution quantitative 13C nuclear magnetic resonance (13C NMR). To compare the test results, a simulation for the pyrolysis reactor was conducted with CHEMCAD software. The result of FTIR analysis showed the presence of carboxylic acids and aliphatic hydroxyl groups, and 13C NMR also shows presence of aromatic C–C and C–O bonds, aliphatic C–O and C–C bonds and carbonyl groups. The experimental results, which were comparable to the simulation, also show that a ratio of 12.5 % zeolite catalyst to waste PET helps the decomposition process and reduces the operating temperature needed in the reactor. There is a positive strong correlation between the reactor temperature and pressure. The highest product yield obtained was 20 % crude oil, 7 % solid powder, 16 % pyrolysis char, and 57 % non-condensable gases.